Extraterrestrial Metaphysics in Process Perspective: Implications of Our Anthropocosmic Nature - Davis, Andrew M. (Zygon, 2025)
This discussion is an exercise in extraterrestrial metaphysics in both theory and practice. In theory, it stresses the nature of the metaphysical endeavor as consisting in the transplanetary exploration of those abiding and indefatigable features of reality that necessarily obtain in any and all possible worlds. In practice, it is a particular expression of extraterrestrial metaphysics on planet Earth. In dialogue with Alfred North Whitehead, Teilhard de Chardin, Charles Hartshorne, and a variety of others, I elaborate process metaphysics as a fruitful, albeit neglected, species of extraterrestrial metaphysics grounded first and foremost in human experience as an anthropocosmic fact of nature. I argue that Life, Mind, and Value are among the ultimate principles and/or categories belonging to the universe and that these principles always find embodiment within a fluid anthropocosmic ontology conceived as living, mind-full, and value-full. I also articulate some of the relevant contours of a process cosmotheology as it relates to process extraterrestrial metaphysics, including some of the metaphysical riddles it addresses and the extraterrestrial plentitude it justifies via divine benevolence. I conclude by extending an invitation to all terrestrial metaphysicians to become more deliberately extraterrestrial in both theory and practice.